Two-Fluid Formulation of Lower-Hybrid Drift Instabilities in Current-Sheet Equilibrium with a Guide Field (Communications in Computational Physics, 2008)
A nonlocal two-fluid formulation has been constructed for describing lower-hybrid drift instabilities in current-sheet configuration with a finite guide magneticfield in the context of magnetic reconnection. As a benchmark and verification, a classof unstable modes with multiple eigenstates are found by numerical solutions withguide field turned off. It is found that the most unstable modes are the electrostatic,short-wavelength perturbations in the lower-hybrid frequency range, with wave functions localized at the edge of the current sheet where the density gradient reaches itsmaximum. It is also found that there exist electrostatic modes located near the centerof the current sheet where the current density is maximum. These modes are low-frequency, long-wavelength perturbations. Attempts will be made to compare the current results with those from kinetic theory in the near future since the validity of thefluid theory ultimately needs to be checked with the more fundamental kinetic theory.